(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, it is mentioned that in the formation of the oil base of cream-perfume soaps based on non-traditional oils, it is effective to combine palm oil with pomegranate seed, grape seed and black seed oils in the proportions of 50:20:20:10 gr/%. It was noted that the color of the obtained oil sample is 80 g J2/100 g, the smell is unique, and the content of vitamin E is 8.98-12.08 mg/100 g higher than other samples. Coupage - (French coupage) is a type of mixing. To improve the quality of the food product, to ensure the typicality of the product and to produce batches that are homogeneous in terms of organoleptic indicators, it is the mixing of its different varieties in a certain proportion.